WATER ENVIRONMENTAL QUALITY AT THE COASTAL AREA OF PHU QUOC ISLAND - Vinh, Le Thi (Vietnam Journal of Marine Science and Technology, 2014)
Data on the water quality at coastal area of Phu Quoc island achieved in May 2010 (dry season) and August 2010 (rainy season) showed that DO concentrations were relatively abundant (>5mg/l), values of BOD5 (<1.96mg/l), COD (<12.5mg/l) and TSS (<42mg/l) were moderate. Concentrations of ammonia (from 0 to 29µgN/l), phosphate (from 4.9 to 17.1µgP/l) and silicate comparatively varied widely, nitrite were always not found. Heavy metal concentrations (Zn <14µg/l, Cu and Pb <4.0µg/l) were fairly low while Fe (from 83 to 282µg/l) and hydrocarbon concentration were comparatively high. In generally, there were no differences in values of basic parameters (DO, pH, TSS), nutrients, heavy metals (Zn, Cu and Pb) and hydrocarbon between two seasons while Fe and BOD values were higher in August 2010. According to criteria for aquatic life protection and coral reef conservation, water quality was relatively good although temperature, nitrate, Fe and oil and grease (both seasons) and phosphate (rainy season) were slightly higher than correspondent critical values. From 2006 to now, water quality at coastal area of Phu Quoc island did not change significantly.